Mathematical notions' approache in early childhood education: analyzing perspectives of brazilian teachers - Warken, Clara Inês (2024)
This study aims to analyze how mathematical notions are worked with children of Early Childhood Education, in Brazilian teachers’ view. The research approach is qualitative and exploratory, and it was developed by the application of an online questionnaire with seventy teachers from five Brazilian regions. The questionnaire answers were analyzed considering three categories: the relationship of the Early Childhood Education teacher with Mathematics; b) the mathematical notions addressed by the teacher and the resources and didactic materials used; and c) what the teacher thinks about his pedagogical practice. Therefore, on the results, we notice that mathematical notions, in Early Childhood Education, are approached through practices that consider games, play, experiences, observations, objects manipulation, and others, as propellers of learning. At this stage, each child peculiarity is considered, as well as their previous knowledge that, associated with playful approaches, stimulate their creativity and interest, making mathematical knowledge possible.